2018
DOI: 10.1016/j.mvr.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Study of microvascular non-Newtonian blood flow modulated by electroosmosis

Abstract: An analytical study of microvascular non-Newtonian blood flow is conducted incorporating the electro-osmosis phenomenon. Blood is considered as a Bingham rheological aqueous ionic solution. An externally applied static axial electrical field is imposed on the system. The Poisson-Boltzmann equation for electrical potential distribution is implemented to accommodate the electrical double layer in the microvascular regime. With long wavelength, lubrication and Debye-Hückel approximations, the boundary value probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Jhorar et al [17] expounded the biomechanical transfer through asymmetric microconduit. Similarly, Tripathi et al [18] inspected the microvascular blood transport via EOF. Francesko et al [19] observed the progress of LOC and microfluidics in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Jhorar et al [17] expounded the biomechanical transfer through asymmetric microconduit. Similarly, Tripathi et al [18] inspected the microvascular blood transport via EOF. Francesko et al [19] observed the progress of LOC and microfluidics in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging nonlinear two-point ordinary differential boundary value problem has been solved with the BVP4C MATLAB numerical code. The present study has ignored electrical field effects which are also relevant to nanofluid materials processing [61,62]. Furthermore, field simulation with computational fluid dynamics software is required for fully three-dimensional flow modelling; these aspects are also being explored [63].…”
Section: Discussionmentioning
confidence: 99%
“…Negative flow refers to the opposite of flow and peristaltic motion, also known as reverse pumping. It was experimentally found in [9] that the blood flow rate decreases exponentially with the passage of time. The authors of that paper also depicted that the deviation of blood flow rate is independent on the structural aspects of the microchannel.…”
Section: Analysis Of Flowmentioning
confidence: 99%
“…In addition, Prakash et al [8] investigated the EOF Williamson ionic nano-liquids in a tapered microfluidic channel under the effects of peristalsis and thermal radiation. Tripathi et al [9] considered the electroosmosis of microvascular blood flow.…”
Section: Introductionmentioning
confidence: 99%